Peculiarities of teaching foreign language in the terms of content and language integrated learning - Zhetpisbayeva, B.A.; Ostdiek, G.; Kitibayeva, A.K. (KSU Publ., 2017)
This article shows the importance of foreign language teaching in the context of the content and language integrated learning; the main problems of teaching a foreign language to students of non-linguistic specialties of universities are discussed, the main challenges of training future professionals of chemistry and biology to the profession are identified. As an example, the specialty "5B072100-Chemical technology of inorganic substances" and the specialty "5B010700-Biotechnology", it is given the calculation of hours allocated to the discipline "Foreign language", according to a standard academic programme. The authors have studied and analyzed scientific and literary sources of Kazakhstani and foreign scientists on the researched topic. The definition of the content and language integrated learning is given where the prospects of its application in the field of higher education are considered. The authors have concluded that the study of a foreign language should be based on an interdisciplinary integrative manner; Training should be aimed at the development of multicomponent general cultural and professional competence of students. In order to implement the concept of CLIL at the level of higher education it is proposed conducting subject courses in a foreign language that would be a good step in language training.
Тіл мен пəнді кіріктіре оқыту тəсілі аясында шетел тіліне оқыту ерекшеліктері
Особенности преподавания иностранного языка в рамках интегрированного подхода к языку и предмету
Keywords: integration; professional competence; sociocultural and professional competencies; professional communication; foreign language for non-linguistic students; transitive; cumulative and determining stages of learning; methodology of content and language integrated learning